An Approach of Legisprudence Theory to Assess the Quality of Local Regulation - Marthen Arie (Faculty of Law, Hasanuddin University, 2016)
The applicable law (as a result of legislation) is not always a reflection of the society concerned. Local regulations in the area were impressed into law to be “forced” because it does not conform to the spirit and characteristics of the society. The formation of local regulation is increasingly complex and complicated when the process and its substance beside cannot be separated from the political process, it is also cannot be separated from social processes. The problematic of local regulation formation is indicated by the fact that the authorized institution to arrange the local regulation is still not sufficient to produce products of high quality local laws. Legisprudence theory may open new perspectives on the validity of norm or legitimacy of norm and by course using this approach the quality of local regulations will be more qualified. Although a political approach is more into the heart in the legislative process but legislation and regulation can be an important object. Legal theory is not only a basis on enforcement or implementation of the rule of law, but it is very useful theory in law-making.